2020
DOI: 10.1038/s41550-020-01222-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular water detected on the sunlit Moon by SOFIA

Abstract: Widespread hydration was detected on the lunar surface through observations of a characteristic absorption feature at 3 µm by three independent spacecraft 1-3. Whether the hydration is molecular water (H 2 O) or other hydroxyl (OH) compounds is unknown and there are no established methods to distinguish the two using the 3 µm band 4. However, a fundamental vibration of molecular water produces a spectral signature at 6 µm that is not shared by other hydroxyl compounds 5. Here, we present observations of the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
132
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 37 publications
20
132
3
3
Order By: Relevance
“…present at high lunar latitudes (Honniball et al, 2020), suggesting that the lunar feature near 3 µm, in that region as well as possibly others, may be a combination of implanted OH and some form of water.…”
Section: Data Availability Statementmentioning
confidence: 91%
“…present at high lunar latitudes (Honniball et al, 2020), suggesting that the lunar feature near 3 µm, in that region as well as possibly others, may be a combination of implanted OH and some form of water.…”
Section: Data Availability Statementmentioning
confidence: 91%
“…During 4-12% of the days at the investigated sites a cumulative water mass of >1 µg per m 2 is released from the surface. This gives rise to the hypothesis that the release of temporarily trapped water could be one potential contributor to recent observations of surface and near-surface water in sunlit areas (Honniball et al, 2020;Pieters et al, 2009). A second mechanism that could lead to such observations is the release of shallow water accumulations via impacts.…”
Section: Daytime Water Releasementioning
confidence: 97%
“…pumping at mid-latitudes and attempt to test a hypothesis for water observations in illuminated nonpolar areas (e.g., Honniball et al, 2020). All six sites have distinct thermal characteristics, representing different boundary conditions for thermal pumping.…”
Section: Investigated Sitesmentioning
confidence: 99%
“…Honniball et al. (2020) recently reported that the lunar regolith holds individual water molecules that could be the result of micrometeoroid impact inducing water formation from hydroxyl. It is interesting to note that the detection in Honniball et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, dielectric breakdown induced by SEP may be a potentially important mechanism for surface water formation in PSRs as well as, to a lesser extent, globally on the Moon. Honniball et al (2020) recently reported that the lunar regolith holds individual water molecules that could be the result of micrometeoroid impact inducing water formation from hydroxyl. It is interesting to note that the detection in Honniball et al (2020) could also be consistent with this study, which shows water molecules attaching to regolith grains after a breakdown event.…”
Section: Discussionmentioning
confidence: 99%